The course of headache in idiopathic intracranial hypertension: a 12‐month prospective follow‐up study. (29th July 2014) - Yri, H. M.; Rönnbäck, C.; Wegener, M.; Hamann, S.; Jensen, R. H.
<x xml:space="preserve">Abstract</x> Background and purpose Our aim was to prospectively describe the course of headache during the first year of idiopathic intracranial hypertension (IIH). Methods Patients with newly diagnosed IIH were consecutively included from December 2010 to June 2013. Treatment according to standard guidelines was initiated. Headache history was obtained by headache diaries and standardized interviews performed at baseline and after 1, 2, 3 and 12 months. Parallel changes in papilledema were assessed by optical coherence tomography (OCT). All patients had comprehensive neuro‐ophthalmological examinations including automated perimetry. Results Forty‐four patients were included. Thirty‐five patients completed the 12‐month follow‐up. Dramatic improvement in headache occurred within the first weeks after diagnosis. After 1 year, 15 patients reported no or only infrequent headache. However, 15 of the remaining 20 patients reported sustained chronic headache. Early age of onset and high diagnostic intracranial pressure (ICP) were associated with better headache outcome (≤1 headache days/month) after a year. Papilledema decreased rapidly within the first 2 months of diagnosis. After 1 year, OCT measures had normalized. Visual outcome was excellent in most patients. Conclusions Although headache in 43% of patients responded well to ICP management, sustained long‐term headache was seen in the remaining patients, despite resolution of papilledema. Headache in IIH may thus be attributed to more complex mechanisms than ICP elevation alone. High ICP and young age were associated with better headache outcome. Early treatment according to standard guidelines seems sufficient to ensure excellent visual outcome in the vast majority of patients.